The Impact of Pharmacogenomics on Postoperative Nausea and Vomiting: Do CYP2D6 Allele Copy Number and Polymorphisms Affect the Success or Failure of Ondansetron Prophylaxis? - Candiotti, Keith A.; Birnbach, David J.; Lubarsky, David A.; Nhuch, Fani; Kamat, Aimee; Koch, Walter H.; Nikoloff, Michele; Wu, Lin; Andrews, David (Anesthesiology (Philadelphia), 2005)
Some patients treated with ondansetron for postoperative nausea and vomiting do not respond to therapy. One possible mechanism for this failure is ultrarapid drug metabolism via the cytochrome P-450 system, specifically the enzyme 2D6 (CYP2D6). Ultrarapid metabolism is seen in patients with multiple functional copies (>/= 3) of the CYP2D6 allele. This study was designed to determine whether patients who were given prophylactic ondansetron and had multiple CYP2D6 alleles had an increased rate of postoperative nausea and vomiting. Two hundred fifty female patients undergoing standardized general anesthesia were given 4 mg ondansetron 30 min before extubation. Patients were observed for symptoms of nausea and vomiting. DNA was extracted from blood in all patients and was analyzed by using a gene-specific probe to determine the CYP2D6 gene copy number and genotyped by polymerase chain reaction amplification with a custom oligonucleotide microarray to determine the specific CYP2D6 genotypes. Eighty-eight patients experienced nausea, and 37 of those patients also had vomiting. In patients with one, two, or three CYP2D6 copies, the incidences of vomiting were 3 in 33 (27%), 27 in 198 (14%), and 7 in 23 (30%), respectively. The incidence of vomiting in subjects with three CYP2D6 copies was significantly different from those with two copies, but not from those with one copy. When analyzed by genotype, the incidences of vomiting in poor, intermediate, extensive, and ultrarapid metabolizers were 1 in 12 (8%), 5 in 30 (17%), 26 in 176 (15%), and 5 in 11 (45%), respectively (P < 0.01 vs. all other groups). There were no differences between groups in the incidence of nausea based on CYP2D6 copy number or genotype. Patients with three copies of the CYP2D6 gene, a genotype consistent with ultrarapid metabolism, or both have an increased incidence of ondansetron failure for the prevention of postoperative vomiting but not nausea.